2004
DOI: 10.1007/s00520-003-0584-z
|View full text |Cite
|
Sign up to set email alerts
|

Nonscheduled consultation in oncologic patients. How many of them are true emergencies? An observational prospective study

Abstract: Oncologic emergencies have been extensively described and clearly defined. In oncology daily practice, cancer patients seek non-scheduled medical care in situations they perceive as a medical emergency, but which may not be a true emergency. The aim of the study was to identify the main symptoms leading to a non-scheduled consultation (NSC) and their relationship to the type of cancer, and to evaluate whether the diagnosis at discharge of patients admitted as result of a NSC correlates with a true oncologic em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 6 publications
(9 reference statements)
1
21
0
Order By: Relevance
“…Patients with gastrointestinal and genitourinary cancers and patients who had never received radiotherapy were more likely to visit the ED with pain as the chief complaint. Our finding that pain was the most frequent reason for cancer patients visiting ED is consistent with previous reports [2,3,5,14]. Despite the prodigious effort dedicated to relieving cancer pain in the two decades since the publication of the World Health Organization analgesic ladder [19], more than 50% of cancer patients across all disease stages still report pain [17,18].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Patients with gastrointestinal and genitourinary cancers and patients who had never received radiotherapy were more likely to visit the ED with pain as the chief complaint. Our finding that pain was the most frequent reason for cancer patients visiting ED is consistent with previous reports [2,3,5,14]. Despite the prodigious effort dedicated to relieving cancer pain in the two decades since the publication of the World Health Organization analgesic ladder [19], more than 50% of cancer patients across all disease stages still report pain [17,18].…”
Section: Discussionsupporting
confidence: 93%
“…However, 32.5% of ED visits made by cancer patients were shown to be avoidable [2], and for those resulting in admission, the true emergency rate was only 26% [3]. The high percentage of ED visits has been recognized as one indicator for poor-quality end-of-life cancer care [1].…”
Section: Introductionmentioning
confidence: 99%
“…The 18 included studies were published between 1995 and 2011 in seven countries: USA (n09), Taiwan (n03), France (n 02), Japan (n 01), Italy (n 01), Australia (n 01), and Argentina (n01) (see Table 4) [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. Seventeen studies were published in English and one in French.…”
Section: Characteristics Of Studiesmentioning
confidence: 99%
“…Although definitions were provided for 16 of the 28 Febrile neutropenia a)Fever (temp >38°C) and profound thrombocytopenia (<20×10 9 /l) [2] b)Absolute granulocyte count <500/mm 3 [5] c)Temperature >38.3°C and suspected neutropenia [12] d)Temp >38°C and absolute neutrophil count <1,000/mm 3 [14] e)Fever ≥100.4°F (in last 24 h) and ANC ≤500 cells/ml [15] f)White blood cell count <1,000/μl (or neutrophils <500/μl) with a core temperature above 38.3°C (or >38°C on 2 consecutive occasions) [16] Sepsis a) Blood: detection of microbial CO 2 by automated method of continuous blood culturing monitoring or urine: >50,000 colony-forming units of pathologic organisms/ml [15] b) Blood lactate >4 mmol/l or low BP (SBP <90 mmHg or 40 mmHg below usual) before fluid challenge or 1+ organ dysfunction (SpO 2 <95 % with fraction of inspired air O 2 >0.5, Cr >176 μmol/l or oliguria, international normalized ratio >2, Bili >78 μmol/l, Glasgow coma scale <15) [ c) Specific to abdominal pain [9] d) Generalized abdominal pain/tenderness, rebounding pain, tenderness localized in the R lower quadrant [17] e) All types of pain [7] Fatigue a) Weakness [5] b) Self-reported on 0-10 scale (severe07-10, non-severe00-6) [ [5] c) Glasgow coma scale score ≤12 [9] Dyspnea a) Shortness of breath [5,13] b) Subjective awareness of difficulty in breathing [11] Skin reactions a) All types of rash, blisters, vesicles, purpura [1] Anemia a) Hb 5.5 g/dl [2] b) Hemoglobin <8 g/dl [11] Infection a) Microbial documentation [2] b) No definition provided, but states 'confirmed' [14] Respiratory failure a) PaO 2 <60 mmHg & RR >30 breaths/min (necessitating mech. vent.)…”
Section: Type Of Symptoms and Adverse Event Definitionsmentioning
confidence: 99%
“…9 One study suggested that the proportion of 'true' emergencies in oncology patients presenting to a hospital emergency department was 26%. 10 Another study suggested that 32.5% of emergency department visits for patients with cancer were potentially avoidable. 11 Studies have consistently shown that pain is the most frequent symptom which prompts emergency department visits in patients with cancer.…”
mentioning
confidence: 99%